Beyond belief: Islamic excursions among the converted peoples - Naipaul, V. S. (New York : Random House, 1998)
Beyond Belief is a book about one of the more important and unsettling issues of our time: the effects of the Islamic conversion of Indonesia, Iran, Pakistan, and Malaysia. It is not a book of opinion. It is - in the Naipaul way - a very rich and human book, full of people and stories.
In Indonesia he finds a pastoral people who have lost their history through a confluence of Islam and technology. In Iran he discovers a religious tyranny as oppressive as the secular one of the Shah, and he meets people weary of the religious rules that govern every aspect of their lives. Pakistan - in a tragic realization of a Muslim re-creation fantasy - inherited blood feuds, rotting palaces, antique cruelty; then President Zia installed religious terror with $100 million of Saudi money.
In Malaysia, the Muslim Youth organization is alive and growing, and the people are mentally, physically, and geographically torn between two worlds, struggling to live the impossible dream of a true faith born out of a spiritual vacancy.
Islam is an Arab religion, and it makes imperial Arabizing demands on its converts. In this way it is more than a private faith, and it can become a neurosis. What has this Arab Islam done to the histories of these converted countries? How do the converted peoples, non-Arabs, view their past - and their future? In a follow-up to Among the Believers, his classic account of his travels through these countries, V. S. Naipaul returns after seventeen years to find out how and what the converted preach.
0
Keywords: Islam; Islam -- Asia; MCE